2018
DOI: 10.1002/jssc.201800326
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive liquid–liquid microextraction combined with dispersive solid‐phase extraction for gas chromatography with mass spectrometry determination of polycyclic aromatic hydrocarbons in aqueous matrices

Abstract: This study describes a dispersive liquid-liquid microextraction combined with dispersive solid-phase extraction method based on phenyl-functionalized magnetic sorbent for the preconcentration of polycyclic aromatic hydrocarbons from environmental water, sugarcane juice, and tea samples prior to gas chromatography with mass spectrometry analysis. Several important parameters affecting the extraction efficiency were investigated thoroughly, including the mass of sorbent, type and volume of extraction solvent, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Extraction efficiency increased with increasing stirring rate, reached its maximum value at 800 rpm and decreased thereafter (figure 3c). This trend is consistent with the results from previous reports, which suggested that stirring promotes proper contact area distribution [36] and increased penetration of mass transfer of the solutes [29]. The decreased extraction efficiency evident at a stirring rate of 1000 rpm may have been owing to the formation of a vortex, which could have resulted in poor contact between the analyte and the extracting solvent [36].…”
Section: Effect Of Stirring Ratesupporting
confidence: 92%
See 1 more Smart Citation
“…Extraction efficiency increased with increasing stirring rate, reached its maximum value at 800 rpm and decreased thereafter (figure 3c). This trend is consistent with the results from previous reports, which suggested that stirring promotes proper contact area distribution [36] and increased penetration of mass transfer of the solutes [29]. The decreased extraction efficiency evident at a stirring rate of 1000 rpm may have been owing to the formation of a vortex, which could have resulted in poor contact between the analyte and the extracting solvent [36].…”
Section: Effect Of Stirring Ratesupporting
confidence: 92%
“…Vibrating sample magnetometer analysis of MNPs were reported previously by our group [29]. royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Characterization Of Magnetic Nanoparticlesmentioning
confidence: 83%
“…LPME includes diverse techniques characterized by small volumes of organic solvents . Three main modes of LPME are single drop microextraction , hollow fiber–liquid phase microextraction , and dispersive liquid–liquid microextraction (DLLME) . DLLME is an important sample preparation method which was firstly performed by Assadi and co–workers .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the matrix's complexity, DLLME applications are limited in solid sample . This analysis method of d‐SPE combined with DLLME has reported for determination of polycyclic aromatic hydrocarbons in aqueous matrices , pesticides (i.e., diazinon, ametryn, chlorpyrifos, penconazole, oxadiazon, diniconazole, and fenazaquin) in fruit juices , organochlorine pesticides (i.e., α‐BHC, β‐BHC, γ‐BHC, δ‐BHC, heptachlor, aldrin, heptachlor epoxide, α‐chlordane, endrin, β‐endosulfan, p,p′‐DDD, endrin aldehyde, and endrin ketone) in vegetables . This method has the advantage of less matrix interference and high enrichment factor, and it has an application prospect for organic contaminants analysis.…”
Section: Introductionmentioning
confidence: 99%